Pemberdayaan UMKM di Sekitar Pantai Carita untuk Manajemen Keuangan, Angsuran dan Resiko Tunggakan Pembayaran Angsuran Dari Permodalan Nasional Madani - Sularso Budilaksono; Rilla Sovitriana; Nana Trinawati; Euis Puspita Dewi; Nurina; Evi Syafrida Nasution (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
Empowerment of Micro, Small and Medium Enterprises (MSMEs) around Carita beach is important in developing the local economy. One aspect that needs attention is financial management and the orderly payment of loan installments whose funding is provided by Permodalan Nasional Madani (PNM) through the Mekar service (Fostering a Prosperous Family Economy). The purpose of the service is to provide knowledge and skills so that MSME actors know about financial management, installments and risks in the event of bad credit. MSMEs that attend are generally MSMEs engaged in processed fish food, chips, chips, chips, crackers etc. The training method provided is by discussion and lecture. The number of MSME participants who attended was 25 people. The result of this dedication is that MSME actors become more knowledgeable about financial management, installments and the risk of bad credit and also MSME production is directly purchased by Collaborative PKM implementers consisting of several lecturers between tertiary institutions.